Role of strong versus weak networks in small business growth in an emerging economy - M. Kamil Kozan; Levent Akdeniz (Administrative Sciences, 2014)
The study tests whether strong rather than weak ties account for small business growth in Turkey. Data were collected by means of a questionnaire filled out by the owners of small firms operating in four cities. Growth is comprised of two main areas, production expansion and knowledge acquisition. Results show that strong ties are positively related to both types of growth. In contrast, loose ties have no effect on small business growth in either area. This finding is attributed to the influence of the collectivistic nature of the mainstream Turkish culture, where owners of small businesses are likely to rely on in-groups rather than out-groups for advice and for financial support. Implications of relative absence of weak ties for small business growth and innovation in emerging economies are discussed. The findings suggest that culture should be included as a contingency variable in future studies of network strength and growth relationship. The paper also discusses the possible moderating role of affective and cognition-based trust in the relation of strong and weak ties to small business growth.
Keywords: 350; small business growth; entrepreneurship; strong ties; weak ties; networks; Turkey